Safety and Efficacy of Subretinal AAV-CRISPR/Cas9 Gene Editing for Rhodopsin-Mutant Retinitis Pigmentosa: A Phase I/IIa Dose-Escalation Triall - Khairiel Anwar; Sony Sanjaya; Rizky Ayu; Fachruddin Sani (Sriwijaya Journal of Ophthalmology, 2025)
Introduction: Autosomal dominant retinitis pigmentosa (adRP) from rhodopsin (RHO) mutations lacks an approved gene therapy. This Phase I/IIa trial evaluated subretinal AAV5-CRISPR/Cas9 for RHO-adRP. Methods: An open-label, 3+3 dose-escalation design with expansion at the recommended Phase II dose (RP2D) was used. Eighteen patients (18 study eyes; one eye per patient) received subretinal AAV5-CRISPR/Cas9 at low (1.5×1010 vg, n = 3), mid (5.0×1010 vg, n = 3), or high (1.5×1011 vg, n = 6) doses, plus an expansion cohort (n = 6) at RP2D, at a private hospital in Palembang, Indonesia. The primary endpoint was dose-limiting toxicities (DLTs); secondary endpoints were BCVA (LogMAR), SD-OCT ellipsoid zone (EZ) width, microperimetry, and ffERG. Results: No DLTs occurred. The high-dose cohort showed a BCVA improvement of −0.14 LogMAR (95% CI −0.22 to −0.06, p = 0.003; Cohen d = 1.82), an EZ width increase of +312 µm (95% CI +187 to +437, p < 0.001; d = 2.45), and a microperimetry gain of +3.8 dB (95% CI +2.1 to +5.5, p < 0.001; d = 1.94). Dose-response trends were significant (Jonckheere–Terpstra p-trend: BCVA 0.008, EZ 0.002). Conclusion: Subretinal AAV5-CRISPR/Cas9 demonstrated acceptable safety with dose-dependent structural and functional improvements at 12 months. Phase II/III trials are warranted.